DEVELOPMENT OF FLOOD MONITORING SYSTEM - AZMAN, DANIAL HANIF (2017)
“Development of flood of monitoring system (DFMS) uses wireless sensor network (WSN) as the technique to monitor the flood. WSN technique is chosen because of the capability to self-healing, self-configuring, and enable to do multi-hopping network, which allows the sensors to be deploy easily. The flood parameters uses are water level, rain rate precipitation, and flow rate of water. This project designed to monitor the flood and alert the responsible authorities when the flood occurs. One of the objectives of the project is to develop working systems, which are user friendly, less energy and cost effectives by using wireless sensor network techniques. The problem with the current system is that, the collection of the data is not constant. A cloud implementation proposed is to store all the data for the further flood prediction analysis. Thus the aim of the system is to develop a flood monitoring system using wireless sensor network providing a constant collection of data with the event-driven of flood.”